The 45o Mediolateral Episiotomy: Does it Reduce to the Incidence of Extended Laceration Incidence and Postlabour Pain? Episiotomi Mediolateral 45 Derajat terhadap Kejadian Perluasan Cedera dan Nyeri Pascasalin pada Primigravida - Frans Yauwena; David Lotisna; Deviana S. Riu; Isharyah Sunarno; Nugraha U. Pellupessy (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: To see the relation between 45 and 60 degrees mediolateral episiotomy to extended laceration incidence and post labor pain in primigravida.Method: The research used simple randomization design which was conducted in the Department of Obstetrics and Gynecology, Teaching Hospital, Faculty of Medicine, Universitas Hasanuddin from April 2018 to September 2018. There were 80 samples for the 45 degrees mediolateral episiotomy group and 80 samples for the 60 degrees group.Result: After the Chi-Square correlation test has been carried out, the research result indicates that there is higher incidence in 60 degrees mediolateral episiotomy group in extended perineal laceration (p=0.002), and Fisher Exact test shows that post labor pain (p=0.000) higher in the same group compared to the 45 degrees group.Conclusion: Mediolateral episiotomy 45 degrees has lower extended perineal laceration and post labor pain compared to the 60 degrees group.Key Words: episiotomy, mediolateral 45, mediolateral 60, perineal laceration, postlabor pain, primigravida Abstrak Tujuan: mengetahui hubungan episiotomi mediolateral 45 dan 60 derajat terhadap kejadian perluasan cedera dan nyeri pasca salin pada primigravida.Metode: simple randomization. Penelitian dilaksanakan di Rumah Sakit Pendidikan Departemen Obstetri dan Ginekologi Fakultas Kedokteran Universitas Hasanuddin periode April 2018–September 2018. Total sampel yang diperoleh adalah 80 untuk kelompok 45 derajat dan 80 sampel untuk kelompok 60 derajat.Hasil: setelah dilakukan uji hubungan dengan Chi Square terdapat hubungan yang signifikan pada episiotomi 60 derajat dengan kejadian perluasan cedera (p=0.002) dan uji Fisher menyatakan hubungan bermakna nyeri pasca salin pada kelompok yang sama (p=0,000) dibandingkan episiotomi 45 derajat. Episiotomi mediolateral 45 derajat memiliki luaran lebih sedikit menyebabkan kejadian perluasan cedera dan nyeri pasca salin dibandingkan episiotomi 60 derajat.Kata kunci: episiotomi, mediolateral 45, mediolateral 60, ruptur perineum, nyeri pasca salin, primigravida